2009
DOI: 10.1590/s1516-89132009000500030
|View full text |Cite
|
Sign up to set email alerts
|

Investigation about the efficiency of the bioaugmentation technique when applied to diesel oil contaminated soils

Abstract: This work investigated the efficiency of the bioaugmentation technique when applied to diesel oil contaminated soils collected at three service stations. Batch biodegradation experiments were carried out in Bartha biometer flasks (250 mL) used to measure the microbial CO 2 production. Biodegradation efficiency was also measured by quantifying the concentration of hydrocarbons. In addition to the biodegradation experiments, the capability of the studied cultures and the native microorganisms to biodegrade the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
7
0
3
Order By: Relevance
“…This result is consistent with the finding of other researchers who found that bioaugmentation was not effective for diesel fuel (Demque, et al, 1997;Mariano, et al, 2009). It is important to note that for both diesel and motor oil-contaminated samples, there was a mean decrease of between 16.8 and 127 ppm TPH for each additional day elapsed between sampling and GC/MS analysis (p-value = 0.05).…”
Section: Statistical Analysis Of Tph Measurementssupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with the finding of other researchers who found that bioaugmentation was not effective for diesel fuel (Demque, et al, 1997;Mariano, et al, 2009). It is important to note that for both diesel and motor oil-contaminated samples, there was a mean decrease of between 16.8 and 127 ppm TPH for each additional day elapsed between sampling and GC/MS analysis (p-value = 0.05).…”
Section: Statistical Analysis Of Tph Measurementssupporting
confidence: 91%
“…Bioaugmentation with Staphylococcus hominis and Kocuria palustris failed to cause any improvement in the degradation of diesel fuel in soil from three gas stations (Mariano, et al, 2009). Bioaugmentation was ineffective and possibly deleterious to diesel biodegradation in sand (Demque, Biggar, & Heroux, 1997).…”
Section: An Added Microbial Inoculum Includingmentioning
confidence: 92%
See 1 more Smart Citation
“…2009). Sometimes unfavourable environmental circumstances, especially during the first days after inoculation, may be a reason that bioaugmentation does not enhance the degradative potential of contaminated soil (Mariano et al. 2009; Silva et al.…”
Section: Discussionmentioning
confidence: 99%
“…What is important, stress because of drastic changes in environmental conditions may lead to loss of microbial viability and even death of inoculated cells (Goldstein et al 1985;van Veen et al 1997;Liu et al 2009). Sometimes unfavourable environmental circumstances, especially during the first days after inoculation, may be a reason that bioaugmentation does not enhance the degradative potential of contaminated soil (Mariano et al 2009;Silva et al 2009;Ruberto et al 2010). A success of microbial survival, phenols removal and subsequently the efficiency of their degradation were strongly correlated with soil organic matter content.…”
Section: Soil Bioaugmentationmentioning
confidence: 99%